STOCHASTIC QUANTIZATION OF FERMIONIC THEORIES - RENORMALIZATION OF THE MASSIVE THIRRING MODEL - Brunelli, J. C. (World Scientific Publ Co Pte Ltd, 1992)
Using the Langevin approach for stochastic processes, we study the renormalizability of the massive Thirring model. At finite fictitious time, we prove the absence of induced quadrilinear counterterms by verifying the cancellation of the divergencies of graphs with four external lines. This implies that the vanishing of the renormalization group beta function already occurs at finite times.